Waste management using the takakura method at the Tingkir Islamic Boarding School, Salatiga - Wina Lutfi; Niken Sukesi (Community Empowerment, 2023)
Central Java province produces the most waste in Indonesia, reaching more than 5 million tons per year. Waste is a complex problem and has a negative impact on environmental sustainability, especially food waste and plastic waste. The purpose of this community service is to reduce the waste volume in temporary shelters, prevent contamination of waste into the environment and build awareness and concern for the environment among Islamic boarding school students. The methods used in community service activities are lectures, demonstrations of making compost using the Takakura method and group discussions attended by 35 students. The results of the program showed an increase in students' knowledge about processing waste into compost (65.8%). The organic compost produced can be used for plant media, fertilizer, business opportunities and additional income for students so that it can be a motivation to produce organic compost from waste management.